2014
DOI: 10.1017/s0007114514002062
|View full text |Cite
|
Sign up to set email alerts
|

Methionine deficiency does not increase polyamine turnover through depletion of hepatic S-adenosylmethionine in juvenile Atlantic salmon

Abstract: During the last few decades, plant protein ingredients such as soya proteins have replaced fishmeal in the diets of aquacultured species. This may affect the requirement and metabolism of methionine as soya contains less methionine compared with fishmeal. To assess whether methionine limitation affects decarboxylated S-adenosylmethionine availability and polyamine status, in the present study, juvenile Atlantic salmon were fed a methionine-deficient plant protein-based diet or the same diet supplemented with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
72
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 45 publications
11
72
2
Order By: Relevance
“…There were no differences in phospholipids or cholesterol between fish fed the three diets in the current trial. No differences in phospholipids are in line with Espe et al () in adult salmon, but not in juvenile salmon where phospholipids increased following increased dietary methionine (Espe et al, ). We were unable to detect any changes in the current trial, this might be due to the relative high variation present between tanks in the current study or simply due to having enough of the vitamins and methionine in the diets to prevent the development of fatty liver.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…There were no differences in phospholipids or cholesterol between fish fed the three diets in the current trial. No differences in phospholipids are in line with Espe et al () in adult salmon, but not in juvenile salmon where phospholipids increased following increased dietary methionine (Espe et al, ). We were unable to detect any changes in the current trial, this might be due to the relative high variation present between tanks in the current study or simply due to having enough of the vitamins and methionine in the diets to prevent the development of fatty liver.…”
Section: Discussionsupporting
confidence: 80%
“…Espe et al () reported increased TAG accumulation in liver of adult salmon fed low methionine diets (6.7 g methionine per kilo diet) of which disappeared when salmon were fed diets containing 9 g methionine per kg diet. On the other hand, juvenile Atlantic salmon fed diets containing low methionine or a methionine‐supplemented diet did not accumulate liver TAG (Espe et al, ), though having a higher relative liver weight and reduced growth are in line with the current trial. The lower protein growth, the elevated FCR and lower retention of indispensable amino acids in the presmolts as compared to postsmolts indicate that presmolt salmon used more of the dietary amino acids for energy purposes than on deposition of muscle protein.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…SAM is a major donor of methyl groups for transmethylation reactions involving nucleic acids and proteins (Lieber and Packer, 2002) as well as aminopropyl groups for the synthesis of polyamines (Espe et al, 2014) which are critical for a range of metabolic processes such as cell proliferation and differentiation . Increased levels of circulating SAM, is likely to provide an advantage in maintaining a rapid rate of growth as seen in those fish in the MetADQ treatment relative to the MetDEF treatment fish in .…”
Section: Methionine Adenosyltransferase (Mat) Catalyses the Formationmentioning
confidence: 99%